Una Mirada Intercultural de Fotoprotección en Estudiantes de Enfermería. - Calderón Cabezas, Carla Cristina (2023)
ABSTRACT: Currently, skin cancer as a public health problem requires facing it through comprehensive, transversal, coherent and sustainable prevention strategies, based on the reality of the individual, family, and community; where previous experiences, beliefs, and customs are included, taking into account the cultural diversity that the Ecuadorian population emanates. The purpose of the study was to determine the intercultural practice of photoprotection in students of the Nursing Career of Universidad Nacional de Chimborazo for the prevention of skin cancer. This research was developed considering the qualitative-interpretive approach, considering narrative and experiential data supported for the in-depth description of the phenomenon. The study subjects constituted 12 key informants who met the inclusion criteria. To collect data, semi-structured interviews and self-reporting with open questions were used until information saturation was reached through videos and recordings, which allowed data to be collected without altering the content. The interviews were transcribed, as well as the categorization, obtaining ideas of highest, medium and low frequency, their interpretation and respective triangulation. The results of this study showed that the intercultural practice of photoprotection in nursing students was related to three central categories: culture/health with the cultural care of photoprotection, environment with the world view and cultural environment, and promotion with the learning needs and /or education on photoprotection respectively. Categories found that are supported by the rising sun model proposed by Madeleine Leininger. Keywords: students, nursing, culture, cultural diversity, skin care